The synergistic effect of cobalt on a Pd/Co catalyzed Suzuki–Miyaura cross-coupling in water. Issue 46 (14th November 2016) - You, Li-Xin; Liu, Hui-Jie; Cui, Lan-Xin; Ding, Fu; Xiong, Gang; Wang, Shu-Ju; Ren, Bao-Yi; Dragutan, Ileana; Dragutan, Valerian; Sun, Ya-Guang
Abstract : We report on the first Suzuki–Miyaura reaction promoted by a phosphine-free trimetallic Pd2 /Co catalyst proceeding in water, under aerobic conditions. Results reveal a synergistic Co–Pd cooperation. Abstract : This work introduces the new trimetallic complex CoPd2 (HBPDC)2 Cl4 ·(H2 O)4 (H2 BPDC = 2, 2′-bipyridine-4, 4′-dicarboxylic acid) as a highly efficient and more cost-effective catalyst for a Suzuki–Miyaura reaction proceeding in water, without additives and under aerobic conditions. Catalytic studies revealed a synergistic Co–Pd cooperativity, fostered by ligation through H2 BPDC, and accounting for the superior performance of the heterobimetallic complex vs. its Co-free counterpart.